The effect of sympathy on discriminatory attitudes toward persons living with HIV/AIDS in Puerto Rico: a hierarchical analysis of women living in public housing - Norman, Lisa R. (2009)
As the number of persons living with HIV/AIDS (PLWHA) continues to increase in Puerto Rico, it becomes increasingly important to address the issues of stigma and other discriminatory attitudes. Therefore, the objective of the present study is to examine the attitudes toward PLWHA of a large sample of women living in public housing in Puerto Rico, including sympathy and support for PLWHA in the workplace and in school. A total of 1138 women completed a self-administered 218-item survey made up of questions that measured HIV-related knowledge, attitudes and behaviors. Levels of sympathy varied depending upon the target group, with HIV-infected drug users receiving the least sympathy. Most women reported that HIV-positive teachers should be allowed to teach and that HIV-positive children should be allowed to attend school. However, a significantly lower percentage reported that HIV-infected nurses should be allowed to continue working. Women who were more sympathetic toward PLWHA were more tolerant of PLWHA in the workplace and school, while those with inaccurate knowledge concerning HIV transmission were less tolerant. Also, those who knew a PLWHA were more tolerant. Levels of discriminatory attitudes in Puerto Rico are high and warrant both individual- and societal-level interventions.